Toxic Workplace Environment, Not Job Stress, as a Predictor of Diminished Nurse Performance in Indonesia - Adzany, Fenindea; Aspiranti, Tasya; Suwarsi, Sri (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
Nurse performance is critical for ensuring hospital services are good.” This study examines the influence of a hazardous work environment and job stress on nurses' work at Cideres Regional Hospital in Majalengka. A cross-sectional approach was employed, and data were collected from 107 inpatient nurses using structured questionnaires with validated instruments. We performed a multiple linear regression analysis to determine the extent to which each of these variables contributed to the prediction. The formulated model is Y = 54.783 − 0.310X₁ − 0.016X₂, where Y represents nursing performance, X₁ represents a toxic working environment, and X₂ represents job stress. The results revealed that working environment toxicity had a strong negative influence on nursing performance (β = –0.310, p < 0.05), indicating that stress does not significantly predict performance. The studies highlighted the value of organizational interventions that address toxic behaviors and promote respectful communication and psychological safety. Investing more effort in enhancing connections between people and leadership practices may have a greater impact on nursing performance than techniques that focus solely on reducing stress. The results indicated that reducing toxicity in the workplace is crucial for enhancing nurse performance and the quality of hospital care.